Analysis of Tree Vegetation and Stored Carbon in Pasir Nunang Village Forest, Southeast Aceh District - Yassir, Muhammad; Akram, Habibul; Yusuf, Husainah; Afkar; Hanum, Erlia (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
To date, no scientific studies have been conducted to determine tree species richness and carbon content in the Pasir Nunang Village Forest, Southeast Aceh Regency, Aceh Province. This study aims to determine the tree species diversity index and carbon content in the Pasir Nunang Village Forest, Southeast Aceh Regency, Aceh Province. Quantitative research then research a purposive sampling method was employed, taking into account variations in topography and slope. Research data sample at the research locations in the north and south were made into plots measuring 40 m x 40 m on the right and left of the transect in a zigzag manner without any intervals of 10 plots, resulting in a total of 20 plots at the research location. Field data collection was conducted from June 22 to July 10, 2024, within the forest area of Pasir Nunang Village, Southeast Aceh Regency. Data collection through observations was conducted on tree stands with a diameter of >20 cm, measuring the tree trunk diameter at chest height of an adult. Data analysis included the calculation of vegetation species diversity index (Shannon–Wiener, H’) and carbon storage was analyzed using allometric equations. The results identified a total of 28 tree species belonging to 16 families, comprising 162 individual trees.The Shannon–Wiener diversity index (H’) reached a maximum value of 3.12. The estimated total aboveground carbon stock in the Pasir Nunang Village Forest was 354.23 tons ha⁻¹.